Mass polarisation: Identification with parliamentary discourses and psychological factors - Afonso, B.; Rosa, C.; Da Silva, R.; Bem-Haj, P. (Behavioral Sciences of Terrorism and Political Aggression, 2024)
Ideological polarisation research has gained prominence due to its growing presence in established democracies and its associated negative consequences. This study aimed to explore the identification with polarised parliamentary discourses in a Portuguese sample and its relationship with psychological factors. Results revealed the absence of mass ideological polarisation and a greater leftist identification. Participants who identified more with the right-wing evidenced greater identity fusion with the country and dogmatism, and less tendency to ruminate and to be verbally aggressive. Participants who identified more with the left-wing showed less identity fusion with the country, less dogmatism and greater capacity for empathy, rumination, tolerance to ambiguity, and verbal aggression. Innovative results were also found on the relationship between greater left-wing identification, identity fusion with the country and verbal aggression.